Efektifitas Pelatihan Kader Kesehatan dalam Penanganan Tuberkulosis di Wilayah Binaan - Elman Boy (Jurnal Pendidikan Kedokteran Indonesia, 2015)
Background: Medan is an area with the largest TB patients in the North Sumatra Province. Since 2014, Medan Denai Distric is a target area of Medical Faculty of University Muhammadiyah North Sumatra (FM UMSU). One of the implemented program is  formulating a Community Forum on TB Care. The objective of this study is to find out the effectiveness of TB management training by improving the knowledge of health cadres.